(untitled) (Eurasian Journal of Ecology, 2024)
The article presents data on the distribution and biological features of the ontogenetic states of Paeonia anomala L. on the territory of Kazakhstan. The distribution of the species was established according to field research, observations, literature and materials of herbarium collections: MW, NUR and AA. The age of the plants was determined by the annual layers on the rhizomes of P. anomala. According to the data obtained, the main distribution area of P. anomala in Kazakhstan is located within the East Kazakhstan region, in the Katon-Karagai, Kurchum, Shemonaikha, Ulan and Zyryanovsky administrative districts. It is much less common in the Zhambyl and Almaty regions, the south-western border of the general distribution area of the species passes in these regions. Our studies have not confirmed the growth of P. anomala on the territory of the Kokchetav upland of the Kazakh small-grassland. The results of the research made it possible to establish in the ontogenesis of P. anomala L. 9 age-related conditions: latent state, seedlings, juvenile, immature, virginal, young generative, mature generative, old generative and senile. Life span of P. anomala in East Kazakhstan is 55-70 years old, sometimes more. In populations confined to the Subalpine belt and sparse forest cenoses, age spectra with an absolute maximum of the age cycle are characteristic. Key words: Paeonia anomala, population, ontogenetic structure, age composition.